Perivascular Accumulation of β-Sheet-Rich Proteins in Offspring Brain following Maternal Exposure to Carbon Black Nanoparticles - Onoda, Atsuto; Kawasaki, Takayasu; Tsukiyama, Koichi; Takeda, Ken; Umezawa, Masakazu (Frontiers in Cellular Neuroscience, 2017)
Environmental stimulation during brain development is an important risk factor for the development of neurodegenerative disease. Clinical evidence indicates that prenatal exposure to particulate air pollutants leads to diffuse damage to the neurovascular unit in the developing brain and accelerates neurodegeneration. Maternal exposure to carbon black nanoparticles (CB-NPs), used as a model for particulate air pollution, induces long-lasting diffuse perivascular abnormalities. We aimed to comprehensively characterize the perivascular abnormalities related to maternal NPs exposure using Fourier transform infrared microspectroscopy (in situ FT-IR) and classical staining analysis. Pregnant ICR mice were intranasally treated with a CB-NPs suspension (95 µg/kg at a time) on gestational days 5 and 9. Brains were collected 6 weeks after birth and sliced to prepare 10-μm-thick serial sections. Reflective spectra of in situ FT-IR were acquired using lattice measurements (x-axis: 7, y-axis: 7, 30-μm apertures) around a centered blood vessel. We also performed mapping analysis of protein secondary structures. Serial sections were stained with using periodic acid-Schiff or immunofluorescence to examine the phenotypes of the perivascular areas. Peaks of amide I bands in spectra from perivascular areas were shifted by maternal NPs exposure. However, there were two types of peak-shift in one mouse in the exposure group. Some vessels had a large peak-shift and others had a small peak-shift. In situ FT-IR combined with traditional staining revealed that the large peak-shift was induced around blood vessel adjacent to astrocytes with glial fibrillary acidic protein and aquaporin-4 over-expression and perivascular macrophages with enlarged lysosome granules. Furthermore, protein secondary structural analysis indicated that maternal NPs exposure led to increases in β-sheet content and decreases in α-helix content in areas that are mostly close to the centered blood vessel displaying histopathological changes. These results suggest that β-sheet-rich waste proteins, which are denatured by maternal NPs exposure, likely accumulate in the perivascular space as they are processed by the clearance systems in the brain. This may in turn lead the denaturation of perivascular macrophages and astrocyte activation. The risk of neurodegeneration may be enhanced by exposure to particulate air pollutants during brain development following the perivascular accumulation of β-sheet-rich waste proteins.